(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2021)
The New Civil Procedure Code innovated the procedural law and, notably, the provisional reliefs. It sought to protect more quickly and effectively the rights of those unable to wait for a final decision, obtained through exhaustive cognition. In addition, it brought to the legal world the institute of the stabilization of the effects of concessive decision of provisional urgent anticipated relief, previously required. However, such as everything that is applied for the first time in the legal order, the stabilization provoked some questions, among them two possible ways for contestation. Thereby, this scientific article aims to understand the provisional relief genre, going deeper into the anticipated relief to then explain the divergence about the stabilization technique and the possible ways of contesting it. To verify the essential questions on the theme, the methodology used will be to research for doctrine and jurisprudence. Therefore, the idea is to present the foundations existing in both opinions, as well as the current jurisprudential position, for the reader to acquire a complete understanding of this procedural novelty and, at the end, understand the feasibility and benefits of accepting other procedural ways to eliminate the stabilization.